2021
DOI: 10.4251/wjgo.v13.i10.1263
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy approach to pancreatic cancer

Abstract: Pancreatic cancer (PC) continues to pose a major clinical challenge. There has been little improvement in patient survival over the past few decades, and it is projected to become the second leading cause of cancer mortality by 2030. The dismal 5-year survival rate of less than 10% after the diagnosis is attributable to the lack of early symptoms, the absence of specific biomarkers for an early diagnosis, and the inadequacy of available chemotherapies. Most patients are diagnosed when the disease has already m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 189 publications
(206 reference statements)
0
6
0
1
Order By: Relevance
“…Several studies have investigated the utility of EV-encapsulated biomarkers for the detection of PDAC (reviewed in 4 , 48 , 49 ). Many of these studies have focused on EV-RNA as a biomarker source and have found that differential expression analysis of specific miRNAs can differentiate between PDAC and non-affected individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the utility of EV-encapsulated biomarkers for the detection of PDAC (reviewed in 4 , 48 , 49 ). Many of these studies have focused on EV-RNA as a biomarker source and have found that differential expression analysis of specific miRNAs can differentiate between PDAC and non-affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…for the presence of disease biomarkers 4 , represents a promising approach for PDAC screening and detection. Typically, nucleic acids or proteins that circulate in a biofluid are analyzed during liquid biopsy; however, isolation of extracellular vesicles (EVs) from a biofluid and characterization of their cargoes, which include nucleic acids and proteins, is gaining interest 4 . Recent studies have explored the use of EV cargoes as biomarkers for PDAC 5 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue biopsy is essential for achieving a definitive diagnosis of pancreatic cancer 36 . Various biopsy techniques are utilised, including FNA guided by imaging modalities such as EUS or CT and surgical biopsies 36 .…”
Section: Gal-3 and Pancreatic Cancermentioning
confidence: 99%
“…Tissue biopsy is essential for achieving a definitive diagnosis of pancreatic cancer 36 . Various biopsy techniques are utilised, including FNA guided by imaging modalities such as EUS or CT and surgical biopsies 36 . These procedures involve the collection of small samples of pancreatic tissue for histopathological examination, aiding in the confirmation of malignancy and determination of tumour type 36 .…”
Section: Gal-3 and Pancreatic Cancermentioning
confidence: 99%
“…If such lesions, which include pancreatic intraepithelial neoplasms, mucinous cystic neoplasms, IPMNs, and others, are surgically removed before they acquire the ability to invade, development of cancer can be impeded [ 29 , 129 ]. Several factors that differentiate PC from other pancreatic conditions and from healthy individuals, such as serum glycolipids and proteins, inflammatory and growth factors, autoantibodies, cytokines and chemokines, adhesion molecules, metabolites and DNA/RNA-based alterations, have been proposed as novel biomarkers for the early diagnosis of PC [ 11 , 13 , 130 ]. However, these have not yet been implemented in clinical practice, since evidence of their clinical value from large-scale studies is still missing [ 131 ].…”
Section: Clinical Significance Of Genomic Alterations In Stoolmentioning
confidence: 99%